Friday and Robinson: life on Esperanza Island. - Tournier, Michel (Knopf, 1972)
A new approach to the Robinson Crusoe story which explores Robinson's psychological as well as physical experiences and introduces a new twist--Friday eventually becomes master of Robinson.